1988
DOI: 10.1111/j.1463-6395.1988.tb00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Adult Gonads and Development and Structure of the Larva of Rhabdopleura normani (Hemichordata: Pterobranchia)

Abstract: Lester, S. M . 1988. Ultrastructure of adult gonads and development and structure of the larva of Rhabdopleuru normani (Hemichordata: Pterobranchia). (Department ol' Biological Sciences. Clemson University, Clemson, SC, U.S.A.) -Acra zool. (Stockh.) 69. 95-109.Sexually mature adults, embryos and larvae of the pterobranch Rhabdopleura normani from Bermuda were studied with light and electron microscopy. The sexes are separate among the zooids of a colony, but a given colony may contain females and males. In zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…There is, however, an earlier report of internal brooding in an enteropneust by Gilchrist (1925), who published a drawing of a single advanced larva within the trunk coelom of an adult female of Xenopleura vivipara (family Harrimaniidae). Some enteropneust species, like Saccoglossus pusillus (Davis, 1908) as well as pterobranch hemichordates in the genera Cephalodiscus (Sciaparelli et al, 2004) and Rhabdopleura (Lester, 1988;Sato et al, 2008), retain early developmental stages in the maternal burrow or tube.…”
Section: Reproductive Biologymentioning
confidence: 99%
“…There is, however, an earlier report of internal brooding in an enteropneust by Gilchrist (1925), who published a drawing of a single advanced larva within the trunk coelom of an adult female of Xenopleura vivipara (family Harrimaniidae). Some enteropneust species, like Saccoglossus pusillus (Davis, 1908) as well as pterobranch hemichordates in the genera Cephalodiscus (Sciaparelli et al, 2004) and Rhabdopleura (Lester, 1988;Sato et al, 2008), retain early developmental stages in the maternal burrow or tube.…”
Section: Reproductive Biologymentioning
confidence: 99%
“…Pterobranchs were first defined as a class in 1877 (Harmer, 1887), but it was not until they were first found in shallow waters that the details of their development were comprehensively described (Stebbing, 1970;Dilly, 1973;Lester, 1988b;Lester, 1988a;. Bateson originally considered enteropneusts to be primitive chordates and therefore informative for understanding the origin of the vertebrates (Bateson, 1886).…”
Section: Introductionmentioning
confidence: 99%
“…The colonies were found to grow on the concave side of disarticulated lamellibranch shells, mostly Glycymeris glycymeris (dog cockle), collected from the seabed at 21-to 24-m depth, 1-2 miles south of Stoke Point in Devon (Stebbing, 1968). Following this discovery, a species of Cephalodiscus (Lester, 1985) and R. normani (Lester, 1988b) were also discovered in shallow water, this time only 0.5-2 m depth in coastal waters of Bermuda. These discoveries have facilitated study of developmental biology in Rhabdopleura.…”
Section: Discovery Of Shallow Water Pterobranchsmentioning
confidence: 97%
“…Of particular interest, it was demonstrated that Rhabdopleura has lecithotrophic planula-like larvae covered by uniformly arranged cilia (Dilly, 1973;Lester, 1988b;Stebbing, 1970). Larval behavior has been observed, and attempts have been made to observe settlement and development of settled stages in both R. compacta (Dilly, 1973) and R. normani (Lester, 1988a).…”
Section: Discovery Of Shallow Water Pterobranchsmentioning
confidence: 99%
See 1 more Smart Citation